Evaluasi Sistem Proteksi Sambaran Petir pada Gedung G dan Gedung Science Learning Center Fakultas Matematika dan Ilmu Pengetahuan Alam - Fadhil, Achmad Reyhan; Syahrir, Syahrir; Putri, Devina Rayzy Perwitasari Sutaji (Progressive Physics Journal, 2023)
As a building that had been used all day G building and Science Learning Center has an active lightning protector system that can arrest electrons on clouds. Therefore, it necessary to evaluate and measure on lightning protector system that installed on both building. Main purpose of this research is to know the efficieny of the lightning protector systems that installed on G building and Science Learning Center, and also to know equivalent area of the lightning protector systems that installed on G building and Science Learning Center. This reasearch was done by evaluate the system based on risk assesment to know that the lightning protector system is needed or not to be installed on the building and then to calculate the equivalent area from lightning protector system to know the effiency of it, and lastly to measuring resistance of the building it needs Earth Resistance Tester (ERT) so it suit the Threshold Value. The result of this research shows that the lightning protector system on G building has the III efficiency level in value is 85% effiecient and equivalent area in range of 30,559 km2, meanwhile on Science Learning Center building shows that lightning protector system has the IV effieciency level, in value is 80% efficient and equivalent area in range of 20,658 km2.